Control de ingreso por servicios de la Lubricadora Víctor Hugo del cantón Babahoyo - Carrasco Carriel, Nadia Liz (2021)
Financial management provides the information necessary for the decision-making process that the managerial level of organizations has to execute, which is why the control of income is an important component for the treatment of financial data corresponding to the activity companies, because it allows determining the level of sales and establishing appropriate investment decisions. The objective of the investigation carried out at the “Víctor Hugo” Lubricator in the city of Babahoyo is to analyze income control, which has been conditioned by the empirical development of administrative functions by internal management, for this reason, They have presented inconveniences in the handling of financial information essential for the performance of business activities. The methodology applied to obtain information is made up of descriptive and field research types, since they allow the detection of the main research findings; The methods applied are: deductive and inductive for the segregated analysis of each of the organizational weaknesses, while the applied technique is the survey, supported by an internal control questionnaire that determines the level of confidence or risk in the management of income from the “Víctor Hugo” Lubricator. The conclusions obtained reveal an empirical administration that prevents an adequate performance of the administrative-financial activities, as well as the cash settlement carried out over long periods of time.